2008
DOI: 10.3382/ps.2007-00295
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Localization in the Turkey Vaginal but not Sperm Storage Tubule Epithelia

Abstract: Elucidating the cellular and molecular mechanisms regulating sperm selection and transport in the vagina of the hen had been the focus of a limited amount of research over the past decade. New observations indicate the presence of nonneuron endocrine cells in the epithelia lining the lumina of the turkey hen vagina and uterovaginal junction. Although no cells in the vagina or uterovaginal junction surface epithelia exhibited argentaffin staining, typical of cells containing neurosecretory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Rzas et al (1991) first demonstrated the presence of serotonin in the chicken oviduct. More recently, serotonin-positive nonneuronal endocrine-like cells have been localized in turkey vaginal and UVJ epithelia, but not the SST epithelia (Bakst and Akuffo, 2008). Similar cells, known as enterochromaffin cells, are observed in the gut epithelium of other species and appear to regulate a local peristaltic reflex (Olsson and Holmgren, 2001).…”
Section: Vagina: Sperm Selection Transport and Storagementioning
confidence: 97%
See 1 more Smart Citation
“…Rzas et al (1991) first demonstrated the presence of serotonin in the chicken oviduct. More recently, serotonin-positive nonneuronal endocrine-like cells have been localized in turkey vaginal and UVJ epithelia, but not the SST epithelia (Bakst and Akuffo, 2008). Similar cells, known as enterochromaffin cells, are observed in the gut epithelium of other species and appear to regulate a local peristaltic reflex (Olsson and Holmgren, 2001).…”
Section: Vagina: Sperm Selection Transport and Storagementioning
confidence: 97%
“…Interestingly, using a computer-assisted sperm motility analysis system, serotonin (at 10 −4 M but not at 10 −6 M) statistically increased turkey sperm curvilinear velocity and tail beat frequency (M. R. Bakst, unpublished results). Thus, in the context of cryptic female choice, serotonin-containing cells in the vagina and UVJ, but not in SST epithelia, may augment local sperm motility, vaginal cilia beat frequency, and smooth muscle activity facilitating sperm transport to the SST (Bakst and Akuffo, 2008).…”
Section: Vagina: Sperm Selection Transport and Storagementioning
confidence: 99%
“…There are two possible factors involved in selection or loss of sperm deposited with vagina. One is the ciliary beat of vaginal epithelial cells to transport them towards the cloaca (Brillard 1993, Bakst & Akuffo 2008. Another is the response of vaginal cells to release some molecules that may affect the sperm survivability.…”
Section: Sperm Survivability and Cytokines In Hen Oviductmentioning
confidence: 99%
“…These sperm are then transported to the infundibulum, the site of fertilization [57]. Such motilityenhancing factors may include changes in environmental pH and neuroendocrine factors such as serotonin [58][59][60][61][62]. Further oxidation of sperm fatty acids, possibly sequestered from the surround milieu, generates the energy required for sperm to respond to such motilityenhancing factors and transcend the oviduct [9,22,55,63].…”
Section: Oviductal Sperm Selection Transport and Storagementioning
confidence: 99%